Intramolecular Metal‐Free N−N Bond Formation with Heteroaromatic Amines: Mild Access to Fused‐Triazapentalene Derivatives. Issue 7 (23rd January 2020) - Daniel, Matthieu; Hiebel, Marie‐Aude; Guillaumet, Gérald; Pasquinet, Eric; Suzenet, Franck
Abstract: Formation of N−N bonds may offer an original approach to various nitrogen‐containing heterocycles with numerous applications. For this purpose, we found that readily available heteroaromatic amines are appropriate substrates for providing an efficient and innovative approach for the formation of N−N bonds in the presence of iodine (III) reagent in very mild conditions. This method makes it possible to synthesize nitrogen rich triazapentalene derivatives exhibiting fluorescent properties, inaccessible with existing approaches. Abstract : Heteroaryl amines are described as readily available substrates for hypervalent iodine promoted N−N bond formation. In contrast to azide or nitro precursors, amines react at room temperature and enable the synthesis of original nitrogen‐rich triazapentalene derivatives exhibiting fluorescent properties (see scheme).